Fatal progression of squamous cell carcinoma 10 years after cadaveric kidney transplantation - I. N. Dymkov; A. V. Smirnov; A. D. Perlina; K. G. Tailer; I. V. Alexandrov (Вестник трансплантологии и искусственных органов)
Various research has shown that non-melanocytic malignant skin lesion is one of the most common post-kidney transplant neoplasms. Multiple lesions and a more aggressive clinical course are more common in kidney transplant patients than in the general population. This paper presents a case of malignant skin neoplasms in a patient 10 years after cadaveric kidney transplantation. The patient received standard 3-component immunosuppression with satisfactory graft function (serum creatinine level remained at 157–178 μmol/L). Scalp neoplasm was removed. Histological examination revealed a morphological picture characteristic of basal cell carcinoma with squamous differentiation. Subsequently, a relapse of the skin neoplasm of the temporal region, as well as new lesions in the frontal region and the skin of the anterior chest wall, were discovered. Despite surgical treatment and close-focus x-ray radiation, the disease rapidly progressed and eventually led to death. Squamous cell carcinoma can progress very rapidly in patients after solid organ transplantation, despite ongoing combination treatment. Perhaps in such cases, it is worth cancelling immunosuppressive therapy completely and removing the kidney graft in order to control progression of the malignant tumor process.